qanda-logo
search-icon
Symbol
apple-logo
google-play-logo

Calculator search results

Formula
Solve the equation
Answer
circle-check-icon
expand-arrow-icon
expand-arrow-icon
expand-arrow-icon
expand-arrow-icon
Calculate the differentiation
Answer
circle-check-icon
expand-arrow-icon
Graph
$y = 2 x + 1$
$x$Intercept
$\left ( - \dfrac { 1 } { 2 } , 0 \right )$
$y$Intercept
$\left ( 0 , 1 \right )$
$y = 2x+1$
$x = \dfrac { 1 } { 2 } y - \dfrac { 1 } { 2 }$
$ $ Solve a solution to $ x$
$y = \color{#FF6800}{ 2 } \color{#FF6800}{ x } + 1$
$ $ Move $ x $ term to the left side and change the sign $ $
$y \color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ x } = 1$
$\color{#FF6800}{ y } - 2 x = 1$
$ $ Move the rest of the expression except $ x $ term to the right side and replace the sign $ $
$- 2 x = 1 \color{#FF6800}{ - } \color{#FF6800}{ y }$
$- 2 x = \color{#FF6800}{ 1 } \color{#FF6800}{ - } \color{#FF6800}{ y }$
$ $ Organize the expression $ $
$- 2 x = \color{#FF6800}{ - } \color{#FF6800}{ y } \color{#FF6800}{ + } \color{#FF6800}{ 1 }$
$\color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ y } \color{#FF6800}{ + } \color{#FF6800}{ 1 }$
$ $ Change the sign of both sides of the equation $ $
$2 x = y - 1$
$\color{#FF6800}{ 2 } \color{#FF6800}{ x } = \color{#FF6800}{ y } \color{#FF6800}{ - } \color{#FF6800}{ 1 }$
$ $ Divide both sides by the same number $ $
$\color{#FF6800}{ x } = \left ( \color{#FF6800}{ y } \color{#FF6800}{ - } \color{#FF6800}{ 1 } \right ) \color{#FF6800}{ \div } \color{#FF6800}{ 2 }$
$x = \left ( \color{#FF6800}{ y } \color{#FF6800}{ - } \color{#FF6800}{ 1 } \right ) \color{#FF6800}{ \div } \color{#FF6800}{ 2 }$
$ $ Convert division to multiplication $ $
$x = \left ( \color{#FF6800}{ y } \color{#FF6800}{ - } \color{#FF6800}{ 1 } \right ) \color{#FF6800}{ \times } \color{#FF6800}{ \dfrac { 1 } { 2 } }$
$x = \left ( \color{#FF6800}{ y } \color{#FF6800}{ - } \color{#FF6800}{ 1 } \right ) \color{#FF6800}{ \times } \color{#FF6800}{ \dfrac { 1 } { 2 } }$
$ $ Multiply each term in parentheses by $ \dfrac { 1 } { 2 }$
$x = \color{#FF6800}{ \dfrac { 1 } { 2 } } \color{#FF6800}{ y } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 1 } { 2 } }$
$\dfrac {d } {d x } {\left( y \right)} = 2$
Calculate the differentiation of the logarithmic function
$\dfrac {d } {d \color{#FF6800}{ x } } {\left( \color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 1 } \right)}$
$ $ Calculate the differentiation $ $
$\color{#FF6800}{ 2 }$
Solution search results
search-thumbnail-y-=2x+1
$y-=2x+1$
10th-13th grade
Other
Have you found the solution you wanted?
Try again
Try more features at Qanda!
Search by problem image
Ask 1:1 question to TOP class teachers
AI recommend problems and video lecture
apple-logo
google-play-logo